The various impacts of using chatbots by media students at Saudi universities (The International Journal of Educational Sciences and Arts, 2025)
The study aims to identify the various impacts of the use of chatbots by media students at Saudi universities, and to reveal the similarities and differences in the various impacts resulting from the use of chatbots by media students in the Kingdom based on demographic variables. The study is a descriptive study and relies on a survey approach. It was applied to a deliberate sample of (300) male and female media students at universities and departments in the Kingdom of Saudi Arabia, comprising (153) males and (147) females. The survey was used as a data collection tool. The study reached a set of results, the most important of which are: The motive "obtaining information" came first among the motivations for media students at Saudi universities to use chatbots, with an arithmetic mean of 2.39. The motive "requesting assistance" came in second place, with an average of 2.21, followed by the motive "filing complaints" in third place, with an average of 2.09.The types of chatbots preferred by media students at Saudi universities varied, according to their percentage weights, as follows: "ChatGPT" ranked first as the most important type of chatbot, with a weighted weight of (505) points (11.31%), followed by "Dreamix" with a weighted weight of (469) points (10.51%), and then "Voicebox" with a weighted weight of (457) points (9.83%).The phrase "The chatbot provided me with the information I needed" topped the list of media students at Saudi universities regarding the desired effects of using a chatbot, with an arithmetic mean of (2.69). In second place came the phrase "The chatbot seems quick to answer inquiries," with a mean of (2.67).The phrase "It provides me with information that I don't know the validity of." topped the list of media students at Saudi universities regarding the undesirable effects of using chatbots, with an arithmetic mean of 2.60. In second place came the phrase "It sometimes provides me with contradictory information," with an average of 2.40.
Keywords: Different Influences; Media Students; Saudi Universities; Chatbot